Wavelet analysis of digital shearing speckle patterns with a temporal carrier - Quan, Chenggen (2011)
Shearography is an optical technique allows direct measurement of deflection derivatives. This paper presents a novel temporal phase analysis technique based on wavelet transform when shearography is applied to measure a continuously deforming object. A series of shearing speckle patterns is captured by a high-speed camera during the deformation. To avoid the phase ambiguity problem, a temporal carrier is generated by a piezoelectrical transducer (PZT) stage in one beam of the modified Michelson interferometer. The intensity variation of each pixel on recorded images is then analyzed along time axis by a robust mathematical tool - complex Morlet wavelet transform. After the temporal carrier is removed, the absolute phase change representing the first-order derivative of the continuous deformation is obtained without the need of temporal or spatial phase unwrapping process. The results obtained by wavelet transform are compared with those from temporal Fourier transform.